Effectiveness of Nautical Learning with Heuristic Strategy in Scientific Approach in terms of Critical Thinking Ability and Representation Flexibility - Makmur Makmur; Poerwanto Poerwanto (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
This study evaluates the effectiveness of implementing Heuristic Strategies within a Scientific Approach in nautical learning, focusing on Collision Prevention Regulations at Sea (P2TL). Despite the material's potential to enhance critical thinking skills and flexibility of representation, research applying Heuristic Strategies in the Scientific Approach still needs to be explored. Employing a quasi-experimental method with experimental and control classes, data collection involves written measurements. Research hypotheses are elucidated through inferential analysis, encompassing normality, homogeneity, and mean similarity tests on learning outcome scores. The results demonstrate that nautical learning with heuristic strategies in a scientific approach surpasses ordinary scientific approaches in fostering critical thinking skills and flexibility of representation. This research significantly contributes to advancing learning methodologies in nautics, particularly reinforcing students' critical thinking and representational flexibility. The implications provide educators with grounds to consider integrating Heuristic Strategies within Scientific Approaches to enhance nautical learning quality, aligning with evolving educational demands and student needs.